Pengembangan Media Pembelajaran Berbasis Sparkol VideoScribe dengan Menerapkan Model Case Method pada Tematik Tema 7 Sub Tema 1 Pembelajaran 3 Kelas V SD - Ummul Huda Harahap; Elvi Mailani; Apiek Gandamana; Daitin Tarigan; Erlinda Simanungkalit (Departement of Mathematics Education, 2023)
This study uses the Research & Development method with the ADDIE development model which consists of five stages, namely the analysis stage (analysis), design (Design), development (development), implementation (Implementation) and evaluation (evaluation). Data collection techniques are observation, interviews, questionnaires and tests. Data analysis techniques, namely qualitative data analysis techniques and quantitative data analysis techniques. This research and development produces Media-Based Learning productsSparkol VidioScribe By Applying the Case Method Model in Thematic Learning Theme 7 Sub Theme 1 Learning 3 Class V SD. This product has been validated by media experts by obtaining a percentage of 90.52% or included in the